2022
DOI: 10.3390/en15176331
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Polygeneration System Based on Biomass, Wind and Solar Energy for Micro-Scale Isolated Communities

Abstract: The availability of freshwater and energy is a serious issue in remote and islanded areas, especially at a small scale, where there may not be the possibility to access the grid and/or water distribution systems. In this context, polygeneration systems operating on the basis of local, renewable energy sources can be an answer to the users’ demand for electricity, heating, cooling, and domestic hot water. The scope of the proposed paper was to investigate, numerically, the energy and economic feasibility of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Thermal heat storage can be subdivided into three categories: sensible, latent, and thermochemical heat storage. However, due to the lack of commercially available thermochemical heat storage solutions, and due to high material costs and unknown lifespan, the most used are sensible and latent heat storage [7].…”
Section: Space Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal heat storage can be subdivided into three categories: sensible, latent, and thermochemical heat storage. However, due to the lack of commercially available thermochemical heat storage solutions, and due to high material costs and unknown lifespan, the most used are sensible and latent heat storage [7].…”
Section: Space Heatingmentioning
confidence: 99%
“…The objective was to identify gaps in the literature, justifying the development of this novel research. Figaj et al [7] developed a system to provide space heating and cooling (using a Rankine cycle), electrical energy, and fresh and domestic hot water to 10 households located in an isolated community, located in Italy. The hybrid system is based on biomass, wind, and solar energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors reported that the energy demand was 3.5 MWh. On Pantelleria Island in Italy, Figaj et al [15] used TRNSYS software to quantitatively examine a hybrid system powered via biomass, solar, wind, and a liquified petroleum gas (LPG) generator for multi-use for 10 families. The findings demonstrate that the suggested system provides excellent primary energy-saving performance in each of the examined situations, with an average saving of more than 94 percent.…”
Section: Hybrid Energy Systems Without Electrical Energy Storagementioning
confidence: 99%
“…In this section, some papers and points related to the multiple uses of energy hybrid systems will be discussed. Studies for the best HRES design to use CHP to meet energy needs were given by Figaj et al [15,16,18], Figaj and Żoł ądek [17], and Figaj [19] for Poland. Figaj et al [15] quantitatively examined a hybrid system powered by biomass/solar/wind/ LPG generators for providing electricity, fresh water, heating, cooling, and domestic hot water for 10 families.…”
Section: Multi-use Of Hybrid Energy Systemsmentioning
confidence: 99%
“…On the other hand, biomass energy generation costs depend on its final use (industrial or domestic processes, heating or electricity). For example, in household applications, the energy from biomass is used in cooking, heating and biomass boilers to produce hot water for the home by burning chips, logs, olive pits, pellets or briquettes [28][29][30]. Meanwhile, in collective applications (industrial process), the cost will depend on the installed thermal power of the thermal plant, piping, maintenance, system operation and price of the biomass source [31][32][33].…”
Section: Wetmentioning
confidence: 99%